IMPLEMENTASI PENDIDIKAN KARAKTER: KASUS DI SEKOLAH DASAR ISLAM TERPADU NURUL ILMI KOTA JAMBI: IMPLEMENTATION OF CHARACTER EDUCATION: THE CASE OF INTEGRATED ISLAMIC ELEMENTARY SCHOOL NURUL ILMI JAMBI - Nursalamah Siagian (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
Character education is now becoming most prominent concept which is considered as a solution to the failure of education in Indonesia, but the implementation of such a model of education in educational institutions has received less attention. This study aims to determine the implementation of character education in integrated Islamic primary school Nurul Ilmi. The study was conducted using qualitative descriptive approach. Data were collected through in-depth interviews, observations and documentations analysis. The results showed that the implementation of character education in schools is carried out in an integrated manner in all subjects, in extracurricular activities, and in the school culture. The implementation also got community participation. The school chooses and emphasizes religious values from eighteen character values set by the Ministry of Education and Culture, to implement in all the school activities. Keywords: Character education, Islamic primary school, education policy, Jambi Pendidikan karakter saat ini menjadi sebuah konsep yang dianggap sebagai solusi atas kegagalan pendidikan di Indonesia, namun perhatian atas implementasi model pendidikan itu di dalam lembaga pendidikan kurang mendapat perhatian. Penelitian ini bertujuan untuk mengetahui implementasi pendidikan karakter di Sekolah Dasar Islam Terpadu Nurul Ilmi. Penelitian dilakukan menggunakan pendekatan kualitatif deskriptif, dengan metode pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan, implementasi pendidikan karakter di sekolah tersebut dilaksanakan secara terintegrasi dalam semua mata pelajaran, kegiatan ekstrakurikuler, budaya sekolah, dan mendapat peran serta masyarakat. Dari delapanbelas nilai karakter yang ditetapkan Kementerian Pendidikan dan Kebudayaan, sekolah ini memilih dan menekankan nilai religius dalam pelaksanaan semua kegiatan di sekolah. Kata Kunci: pendidikan karakter, sekolah dasar Islam, kebijakan pendidikan, Jambi